INVESTIGATION OF LAUNCHING PROCESS FOR STEEL REINFORCED CONCRETE FRAMEWORK OF LARGE BRIDGES - V. A. Grechukhin; A. Yu. Losev (Наука и техника)
Bridges are considered as the most complicated, labour-consuming and expensive components in roadway network of the Republic of Belarus. So their construction and operation are to be carried out at high technological level. One of the modern industrial methods is a cyclic longitudinal launching of large frameworks which provide the possibility to reject usage of expensive auxiliary facilities and reduce a construction period. There are several variants of longitudinal launching according to shipping conditions and span length: without launching girder, with launching girder, with top strut-framed beam in the form of cable-stayed system, with strut-framed beam located under span. While using method for the cyclic longitudinal launching manufacturing process of span is concentrated on the shore. The main task of the investigations is to select economic, quick and technologically simple type of the cyclic longitudinal launching with minimum resource- and labour inputs. Span launching has been comparatively analyzed with temporary supports being specially constructed within the span and according to capital supports with the help of launching girder. Conclusions made on the basis of calculations for constructive elements of span according to bearing ability of element sections during launching and also during the process of reinforced concrete plate grouting and at the stage of operation have shown that span assembly with application of temporary supports does not reduce steel spread in comparison with the variant excluding them. Results of the conducted investigations have been approbated in cooperation with state enterprise “Belgiprodor” while designing a bridge across river Sozh.